Microwave-controlled generation of shaped single photons in circuit quantum electrodynamics - Pechal, M.; Huthmacher, L.; Zeytinoglu, S.; Abdumalikov, A. A.; Berger, S.; Wallraff, Andreas J; Filipp, Stefan; Eichler, Christopher (Physical Review X, 2014)
Large-scale quantum information processors or quantum communication networks will require reliable exchange of information between spatially separated nodes. The links connecting these nodes can be established using traveling photons that need to be absorbed at the receiving node with high efficiency. This is achievable by shaping the temporal profile of the photons and absorbing them at the receiver by time reversing the emission process. Here, we demonstrate a scheme for creating shaped microwave photons using a superconducting transmon-type three-level system coupled to a transmission line resonator. In a second-order process induced by a modulated microwave drive, we controllably transfer a single excitation from the third level of the transmon to the resonator and shape the emitted photon. We reconstruct the density matrices of the created single-photon states and show that the photons are antibunched. We also create multipeaked photons with a controlled amplitude and phase. In contrast to similar existing schemes, the one we present here is based solely on microwave drives, enabling operation with fixed frequency transmons.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Quantum physics